Determination of Oligopeptide Diversity within a Natural Population of Microcystis spp. (Cyanobacteria) by Typing Single Colonies by Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry - Fastner, Jutta (American Society for Microbiology, 2001)
Besides the most prominent peptide toxin, microcystin, the cyanobacteria Microcystis spp. have been shown to produce a large variety of other bioactive oligopeptides. We investigated for the first time the oligopeptide diversity within a natural Microcystis population by analyzing single colonies directly with matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF MS). The results demonstrate a high diversity of known cyanobacterial peptides such as microcystins, anabaenopeptins, microginins, aeruginosins, and cyanopeptolins, but also many unknown substances in the Microcystis colonies. Oligopeptide patterns were mostly related to specific Microcystis taxa. Microcystis aeruginosa (Kütz.) Kütz. colonies contained mainly microcystins, occasionally accompanied by aeruginosins. In contrast, microcystins were not detected in Microcystis ichthyoblabe Kütz.; instead, colonies of this species contained anabaenopeptins and/or microginins or unknown peptides. Within a third group, Microcystis wesenbergii (Kom.) Kom. in Kondr., chiefly a cyanopeptolin and an unknown peptide were found. Similar patterns, however, were also found in colonies which could not be identified to species level. The significance of oligopeptides as a chemotaxonomic tool within the genus Microcystis is discussed. It could be demonstrated that the typing of single colonies by MALDI-TOF MS may be a valuable tool for ecological studies of the genus Microcystis as well as in early warning of toxic cyanobacterial blooms.